Analysis and synthesis of small ruminant production systems - Smith, G.; Carles, A.B.; Schwartz, J.; Blackburn, A.; Ruvuna, F.; Cartwright, T.C. (1982)
Data collected in the Mt. Kulal area of the Marsabit district by the Integrated Project in Arid Lands (IPAL) are being analyzed for use in simulation studies. Weight, lactation, reproduction, health and forage quality and availability data were collected from flocks of Galla goats and Somali sheep over a two year period. Large year differences were observed in initial analysis of both the sheep and goat data. There was a reduction in birth percentage and milk production in the second year. The heavier female body was inconsistent with the other data or knowledge of actual forage quality and availability.